Property and shape modulation of carbon fibers using lasers - Blaker,JJ; Anthony,DB; Tang,G; Shamsuddin,SR; Kalinka,G; Weinrich,M; Abdolvand,A; Shaffer,MSP; Bismarck,A (ACS Applied Materials & Interfaces, 2016)
An exciting challenge is to create unduloid-reinforcing fibers with tailored dimensions to produce synthetic composites with improved toughness and increased ductility. Continuous carbon fibers, the state-of-the-art reinforcement for structural composites, were modified via controlled laser irradiation to result in expanded outwardly tapered regions, as well as fibers with Q-tip (cotton-bud) end shapes. A pulsed laser treatment was used to introduce damage at the single carbon fiber level, creating expanded regions at predetermined points along the lengths of continuous carbon fibers, whilst maintaining much of their stiffness. The range of produced shapes was quantified and correlated to single fiber tensile properties. Mapped Raman spectroscopy was used to elucidate the local compositional and structural changes. Irradiation conditions were adjusted to create a swollen weakened region, such that fiber failure occurred in the laser treated region producing two fiber ends with outwardly tapered ends. Upon loading the tapered fibers allow for viscoelastic energy dissipation during fiber pull-out by enhanced friction as the fibers plough through a matrix. In these tapered fibers, diameters were locally increased up to 53%, forming outward taper angles of up to 1.8°. The tensile strength and strain to failure of the modified fibers were significantly reduced, by 75% and 55%, respectively, ensuring localization of the break in the expanded region; however, the fiber stiffness was only reduced by 17%. Using harsher irradiation conditions, carbon fibers were completely cut, resulting in cotton-bud fiber end shapes. Single fiber pull-out tests performed using these fibers revealed a 6.75 fold increase in work of pull-out compared to pristine carbon fibers. Controlled laser irradiation is a route to modify the shape of continuous carbon fibers along their lengths, as well as to cut them into controlled lengths leaving tapered or cotton-bud shapes.